REQUIREMENTS FOR PASSENGER INFORMATION IN PUBLIC TRANSPORT - Palo, Jozef (Doprava a spoje, 2008)
The article deals with passenger information in public transport. Passenger information is generally expected to improve the quality of transit service by improving the passenger experience. Passenger information may grant passengers a better sense of control over their trip-making decisions and/or enable them to take action to minimize their waiting times at stops, plan their transfer connections and thus reduce their overall travel time.